Project Approach to the Implementation of Individual Educational Paths in Modern University - Yu. V. Daneykin; O. E. Kalpinskaya; N. G. Fedotova (Высшее образование в России)
The article discusses the project approach to the implementation of individual educational trajectories (IET) in modern Russian university. The relevance of the study stems from the lack of effective models of individualization of the educational process in higher education. The aim of this work is to analyze the project approach as a key subjective factor in the implementation of individual educational paths in the structure of a modern university. The interdisciplinary methodology lies as the basis of the study, which allows integrating the educational practices of higher education in a single context at the fundamental level and achieving a synergistic effect in their implementation. The majority of modern scientific works are devoted either to the problems of individualization of higher education, or to the implementation of project activities at a university, without a detailed analysis of the correlations of these concepts of modern educational discourse.As results, the article presents the key principles of the project approach to the implementation of IET (systemicity, teamwork, interaction with the external environment, digital transformation of the learning process, staffing of project work), as well as a list of issues requiring discussion by the scientific community exploring modern educational practices of higher education in Russia. The authors emphasize that the project approach to the implementation of IEP in higher education can be considered as a special technique based on the competency-based approach to individualization of education and focusing on the active position of the student to recognize educational deficits and make an individual choice of the educational route, to see and comprehend the directions of competency-based growth and self-development. The awareness of individualization of learning is determined by the project approach, while the individual educational path becomes more conscious and logical for the student, provoking his (her) educational needs and providing the need for the development of certain competencies. The results of the study were used by the authors to develop and implement an adaptive model for constructing individual educational trajectories at the Yaroslav-the-Wise Novgorod State University.